Strongly-coupled quantum critical point in an all-in-all-out antiferromagnet - Yishu Wang (Nature Portfolio, 2018)
The critical behavior of a continuous phase transition is determined by both symmetry and dimensionality. Wang et al. present evidence that the cubic all-in-all-out spin order in Cd2Os2O7 leads to a realization of a non-mean-field strongly-coupled quantum phase transition in three dimensions.